Optimized submerged batch fermentation for metabolic switching in Streptomyces yanglinensis 3–10 providing platform for reveromycin A and B biosynthesis, engineering, and production - Yang, Longyan; Shakeel, Qaiser; Xu, Xueqin; Ali, Liaqat; Chen, Zhiyan; Mubeen, Mustansar; Sohail, Muhammad Aamir; IfItikhar, Yasir; Kumar, Ajay; Solanki, Manoj Kumar; Zhou, Yun; Zhao, Dongling; et al. (Frontiers in Microbiology, 2024)
The cultivation system requires that the approach providing biomass for all types of metabolic analysis be of excellent quality and reliability. This study was conducted to enhance the efficiency and yield of antifungal substances (AFS) production in Streptomyces yanglinensis 3-10 by optimizing operation conditions of aeration, agitation, carbon source, and incubation time in a fermenter. Dissolved oxygen (DO) and pH were found to play significant roles in AFS production. The optimum pH for the production of AFS in S. yanglinensis 3-10 was found to be 6.5. As the AFS synthesis is generally thought to be an aerobic process, DO plays a significant role in it. The synthesis of bioactive compounds can vary depending on how DO affects growth rate. This study validates that the high growth rate and antifungal activity required a minimum DO concentration of about 20% saturation. The DO supply in a fermenter can be raised once agitation and aeration have been adjusted. Consequently, DO can stimulate the development of bacteria and enzyme production. A large shearing effect could result from the extreme agitation, harming the cell and deactivating its products. The highest inhibition zone diameter (IZD) was obtained with 3% starch, making starch a more efficient carbon source than glucose. Temperature is another important factor affecting AFS production. The needed fermentation time would increase and AFS production would be reduced by the too-low operating temperature. Furthermore, large-scale fermenters are challenging to manage at temperatures far below room temperature. According to this research, 28°C is the ideal temperature for the fermentation of S. yanglinensis 3-10. The current study deals with the optimization of submerged batch fermentation involving modification of operation conditions to effectively enhance the efficiency and yield of AFS production in S. yanglinensis 3-10.